Exosomes and exosome composite scaffolds in periodontal tissue engineering - Wang, Tingyu; Zhou, Yanxing; Zhang, Wenwen; Xue, Yuanye; Xiao, Ziteng; Zhou, Yanfang; Peng, Xinsheng (Frontiers in Bioengineering and Biotechnology, 2024)
Promoting complete periodontal regeneration of damaged periodontal tissues, including dental cementum, periodontal ligament, and alveolar bone, is one of the challenges in the treatment of periodontitis.Therefore, it is urgent to explore new treatment strategies for periodontitis. Exosomes generated from stem cells are now a promising alternative to stem cell therapy, with therapeutic results comparable to those of their blast cells. It has great potential in regulating immune function, inflammation, microbiota, and tissue regeneration and has shown good effects in periodontal tissue regeneration. In addition, periodontal tissue engineering combines exosomes with biomaterial scaffolds to maximize the therapeutic advantages of exosomes. Therefore, this article reviews the progress, challenges, and prospects of exosome and exosome-loaded composite scaffolds in periodontal regeneration.